TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN SELF EFFICACY BELAJAR SISWA - Harwanti Noviandari; Jawahirul Kawakib (Ilmu Psikologi Universitas Yudharta Pasuruan)
Adolescent experience a variety of changes both physically and psychologically that can cause teens to feel anxious, confused, worried. Changes that occur can lead to various problems in adolescents is one of them is the lack of adolescent confidence in their own ability to produce an achievement in a particular situation. This makes adolescent students require self-efficacy in learning. Referring to the description of this study examines the effectiveness of cognitive restructuring techniques in improving self-efficacy of students learning class X APK SMK PGRI Rogojampi School Year 2016/2017. Data collection to reveal self efficacy using self efficacy scale, while cognitive restructuring technique is given as treatment in the experimental group. Data analysis for self efficacy variable by using t-statistic analysis. The results of this study indicate that there is a significant increase of the results of pretest score and posttest score in the experimental group with a difference of 49.57 average value after being given treatment in the form of cognitive restructuring technique. While the control group did not increase significantly, the difference between the average value of pretest and posttest was only 17.5. The results of this study can be seen that group counseling with cognitive restructuring techniques effective in improving self-efficacy learners class X APK SMK PGRI Rogojampi Academic Year 2016/2017.